Comparison between improved histogram shifting and LSB (bit-plan mapping) in digital watermarking techniques - Ahmed Mahmood, Omar; Sabeeh Yousif, Ahmed; Y.H. Ahmed, Falah (International Journal of Engineering and Technology, 2019)
Editing, reproduction and delivery of the digital multimedia are becoming particularly easier and closer with the existence of the internet and the availability of pervasive and strongly multimedia tools. Digital watermarking has emerged as a possible method to address these issues. For the proposed Histogram Shifting, modification of the histogram and shifting is applied for embedding the stage; furthermore the contribution in this method incorporated the threshold concept to improve the visual quality of the host image. The performance of the proposed watermarking schemes has been evaluated by using the watermarked images (standard images) of size 512×512 (gray scale) with a different amount of variables "random bit streams" used in the histogram sniffing. The simulations are performed in MATLAB 7 software environment and the visual quality of output image measured by PSNR metric. A comparison is made between the results of the proposed algorithm with the best method namely LSB (Bit Plane Mapping) method and demonstrates that the proposed method is superior in performance in visual quality factor.
Keywords: Digital Watermarking Concepts; Histogram Shifting (HS); Human Visual Quality; LSB Method.